Analisis Hubungan Kecepatan Gelombang Dengan Kuat Tekan Beton Menggunakan Metode UPV - Anggia Eta Rizkiasari; Abdul Rouf (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Until now the use of concrete as a building material is still widely used for building structures. It is important to do concrete compressive strength testing as one of the factors to know the quality of a concrete. NDT (Non-Destructive Testing) is a method of solid quality testing without damaging the object. Testing with the NDT method is considered more efficient than the destructive test method. One method for performing NDT testing is by utilizing UPV (Ultrasonic Pulse Velocity).UPV is a method for estimating concrete compressive strength based on the ultrasonic pulse velocity relationship through concrete with the concrete compressive strength itself. UPV testing works by emitting ultrasonic pulses of 40 kHz through concrete to obtain the travel time of the pulse. Then the resulting time will be calculated the value of its speed and then will be converted into concrete compressive strength.Concrete compressive strength measurement system for high-quality concrete using UPV method can be designed by utilizing relation between ultrasonic pulse velocity with concrete compressive strength. Based on the test results, the average error value of concrete compressive strength testing is 3.04% with a maximum error of 6.63%.